Electrochemical reduction of cationic Li+@C60 to neutral Li+@C60˙−: isolation and characterisation of endohedral [60]fulleride. Issue 9 (28th June 2016) - Ueno, Hiroshi; Aoyagi, Shinobu; Yamazaki, Yu; Ohkubo, Kei; Ikuma, Naohiko; Okada, Hiroshi; Kato, Tatsuhisa; Matsuo, Yutaka; Fukuzumi, Shunichi; Kokubo, Ken
Abstract : Li@C60 was synthesised by electrochemical reduction of ionic Li + @C60 salt. This is the first report of isolation and unambiguous characterisation of endohedral metallo[60]fullerene. Abstract : Lithium-encapsulated [60]fullerene Li@C60, namely, lithium-ion-encapsulated [60]fullerene radical anion Li + @C60 ˙ −, was synthesised by electrochemical reduction of lithium-ion-encapsulated [60]fullerene trifluoromethanesulfonylimide salt [Li + @C60 ](TFSI − ). The product was fully characterised by UV-vis-NIR absorption and ESR spectroscopy as well as single-crystal X-ray analysis for the co-crystal with nickel octaethylporphyrin. In solution Li@C60 exists as a monomer form dominantly, while in the crystal state it forms a dimer (Li@C60 –Li@C60 ) through coupling of the C60 radical anion cage. These structural features were supported by DFT calculations at the M06-2X/6-31G(d) level of theory.